Managing Earnings V/S Strategizing Dividends: Sectoral Evidence from Pakistan Stock Exchange - Farhan Ahmed; Javed Ahmed (Universitas Pelita Harapan, 2018)
This paper means to inspect the regression between the Price to Book ratio as a proxy for earning management and payout proportion as a proxy to dividend policy. This paper utilizes multivariate analysis to examine the relationship between the price to book ratio and dividend policy. Using 11 years’ annual data from 2006-2016, this paper delivers new confirmation demonstrating that timely payment of dividend has a positive impact on the reputation of the company in the market. Dividend payment boosts up investors’ confidence to invest in the company. This study helps the corporate superintendents and stock financial experts to focus on the relationship of the dividend. No past review has handled the issue of the contingent relationship between the price to book ratio and payout proportion in Pakistani Industry and specifically on cement, food and oil and gas sectors.Abstrak dalam Bahasa Indonesia : Tulisan ini bermaksud untuk meneliti regresi antara Price to Book Ratio sebagai proksi untuk manajemen penghasilan dan proporsi pembayaran sebagai proksi untuk kebijakan dividen.Penelitian ini menggunakan analisis multivariat untuk menguji hubungan antara Price to Book Ratio dan kebijakan dividen. Dengan menggunakan data tahunan selama 11 tahun dari 2006-2016, artikel ini memunculkan suatu konfirmasi yang menunjukkan bahwa pembayaran dividen tepat waktu memiliki dampak positif pada reputasi perusahaan di pasar. Pembayaran dividen meningkatkan kepercayaan investor untuk berinvestasi di perusahaan. Studi ini membantu pengawas perusahaan dan ahli keuangan saham untuk fokus pada hubungan dividen. Belum ada penelitian sebelumnya yang menangani masalah hubungan kontingen antara Price to Book Ratio dan proporsi pembayaran dalam Industri di Pakistan dan khususnya pada sektor semen, pangan dan minyak dan gas.